Potential health advantages of Periploca laevigata: Preliminary phytochemical analysis and evaluation of in vitro antioxidant capacity and assessment of hepatoprotective, anti-inflammatory and analgesic effects. (September 2018) - Tlili, Nizar; Tir, Meriam; Feriani, Anouar; Yahia, Yassine; Allagui, Mohamed Salah; Saadaoui, Ezzeddine; El Cafsi, Mhammed; Nasri, Nizar
Graphical abstract: Highlights: Protein, oil, and phenolic compounds of Periploca laevigata seeds were determined. LC-ESI-MS analysis revealed the presence of eighteen identified molecules. Samples exhibited an antioxidant capacity. In vivo tests revealed hepatoprotective, anti-inflammatory and analgesic effects. Abstract: The goal of the present work was a phytochemical screening together with the study of a possible hepatoprotective, anti-inflammatory and analgesic effects of Periploca laevigata seeds extract. Soxhlet extraction revealed that the oil content was ca. 5.5% DW and Kjeldhal method revealed that the protein level was ca. 22% DW. Phenolic compounds, flavonoids and condensed tannin contents were 21.2 mg GAE/g DW, 1.65 mg QE/g DW and 0.58 mg CE/g DW, respectively. LC-ESI-MS analysis revealed the presence of eighteen identified molecules and the most dominant compounds were quinic acid (ca. 3700 µg/g DW) and gallic acid (ca. 3050 µg/g DW). Pretreatment with P. laevigata extract ameliorated levels of serum parameters for liver together with oxidative stress indicators and antioxidant enzymes activities. Anti-inflammatory and analgesic studies showed that P. laevigata extract reduced carrageenan-induced oedema and acetic acid-induced abdominal writhing, and increased latency in hot plate test.